Modelos Matemáticos e Métodos de Solução para Problemas de Dimensionamento de Lotes - Fiorotto, Diego Jacinto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The lot sizing problem is a production optimization problem and consists of determining the quantity of products to be produced in each period of a nite time horizon, in order to meet the demand and optimize an objective function, for example, to minimize costs. In this thesis we address two di erent extensions of the standard lot sizing problem. In the rst part we consider the capacitated lot-sizing problem with multiple items, setup time and unrelated parallel machines and, in the second one, the capacitated lot sizing problem with multiple items and setup crossover. For the rst part of this thesis where we study the lot sizing problem with unrelated parallel machines, the aim is to apply di erent solution methods that use Lagrangian relaxation and Dantzig-Wolfe decomposition to obtain high quality lower bounds and develop Lagrangian heuristics to obtain good feasible solutions (upper bounds). Based on a strong reformulation of the problem as a shortest path problem and unlike in the traditional approach in which the linking constraints are the capacity constraints, we use the ow constraints, i.e. the demand constraints, as linking constraints. The aim of this approach is to obtain high quality lower bounds and for this we have used three di erent solution methods. In the rst one the Lagrangian relaxation is applied to the ow constraints. For the other two we solve the master problem applying solution methods that combine Lagrangian relaxation and Dantzig-Wolfe decomposition in a hybrid form. Two primal heuristics, based on transfers of production quantities, are used to generate feasible solutions. Computational experiments using data sets from the literature are presented and show that the solution methods produce lower bounds of excellent quality and competitive upper bounds, when compared with the bounds produced by other methods from the literature and by a high-performance MIP software...

O problema de dimensionamento de lotes é um problema de otimização da produção e consiste em determinar a quantidade de produtos a serem produzidos em cada período ao longo de um horizonte de tempo nito, de modo a atender uma demanda e otimizar uma função objetivo, por exemplo, minimizar os custos. Esta tese aborda duas extensões diferentes do problema de dimensionamento de lotes padrão. Na primeira parte, considerase o problema de dimensionamento de lotes com vários itens, tempos de preparação e máquinas paralelas distintas, e na segunda parte, o problema de dimensionamento de lotes com vários itens e preparação crossover. Para a primeira parte desta tese, em que estuda-se o problema de dimensionamento de lotes com máquina paralelas, o objetivo é aplicar diferentes métodos de solução que utilizam relaxação Lagrangiana e decomposição de Dantzig-Wolfe para obter limitantes inferiores de alta qualidade e desenvolver heurísticas Lagrangianas para obter boas soluções factíveis (limitantes superiores). Baseado em uma reformulação forte do problema como um problema de caminho mínimo e diferente da abordagem tradicional em que as restrições de ligação são as restrições de capacidade, utiliza-se as restrições de uxo, isto é as restrições de demanda, como as restrições de ligação. O objetivo desta abordagem é obter limitantes inferiores de alta qualidade e para tanto, utiliza-se três métodos de solução diferentes. No primeiro a relaxação Lagrangiana é aplicada as restrições de uxo. Para os outros dois resolve-se o problema mestre aplicando métodos de solução diferentes que combinam relaxação Lagrangiana e decomposição de Dantzig-Wolfe de forma hibrida. Duas heurísticas primais, baseadas em transferências de produção, são utilizadas para gerar soluções factíveis. Experimentos computacionais utilizando conjuntos de dados da literatura são apresentados e mostram que os métodos de...
Keywords: Computação; Matemática; Modelos matematicos; Problema de dimensionamento de lotes; Planejamento experimental